The Impact of English Content on TikTok on Developing Student’s Oral Communication Competence - Christafvilia Permata Tangibali; Nur Aeni; Muhalim Muhalim (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2026)
This study aims to analyze the impact of English content on the TikTok application on students' oral communication competence. A mixed-method approach with convergent parallel design was employed, combining quantitative data from pre-tests and post-tests, and qualitative data from interviews. The sample consisted of 36 students from class XI-H selected through cluster random sampling at SMAN 13 Makassar for pre-test and post-test testing and purposive sampling for the interviews with students who shows a significant improvement on test. The results showed that the average score obtained by students in the pre-test was 53 (categorized as ‘Poor’), while the average post-test score was 66 (categorized as ‘Enough’). While the interview data shows that the combination of audio-visual English content on TikTok helps students clearly understand the use of sentences or phrases according to the context and the correct pronunciation in a more engaging way. It can be concluded that there is a significant impact of exposure to English content on TikTok on students’ oral communication competence.